Phytocannabinoids: General Aspects and Pharmacological Potential in Neurodegenerative Diseases - dos Reis Rosa Franco, Graziella; Smid, Scott; Viegas, Cláudio (Current Neuropharmacology, 2021)
In the last few years research into Cannabis and its constituent phytocannabinoids has burgeoned, particularly in the potential application of novel cannabis phytochemicals for the treatment of diverse illnesses related to neurodegeneration and dementia, including Alzheimer’s (AD), Parkinson’s (PD) and Huntington’s disease (HD). To date, these neurological diseases have mostly relied on symptomatological management. However, with an aging population globally, the search for more efficient and disease-modifying treatments that could delay or mitigate disease progression is imperative. In this context, this review aims to present state of the art in the research with cannabinoids and novel cannabinoid-based drug candidates that have been emerged as novel promising alternatives for drug development and innovation in the therapeutics of a number of diseases, especially those related to CNS-disturbance and impairment.
Keywords: endocannabinoid system